Serum levels of soluble CD30 in adult patients affected by atopic dermatitis and its relation to age, duration of disease and Scoring Atopic Dermatitis index - Gabriele Di Lorenzo; Sebastiano Gangemi; Rosaria Alba Merendino; Paola Lucia Minciullo; Serafina Paola Cannavò; Nicola Martinelli; Pasquale Mansueto; Giovanni Battista Rini; Roberto Corrocher; Maria Luisa Pacor (Mediators of Inflammation)
The value of CD30 and the soluble circulating fragment of CD30 (sCD30) for atopic dermatitis (AD) remains unclear. In particular, little is known about the effects of age, duration of disease and Scoring Atopic Dermatitis index (SCORAD) on the levels of serum sCD30 in patients affected by AD. In the present study, we have analysed serum sCD30 levels of adult patients affected by AD. The study's population includes 18 non-smoking outpatients, with a diagnosis of AD. As a control group we studied 18 non-atopic subjects from laboratory staff, matched for sex and age. These subjects had no history of AD, urticaria or seasonal or perennial rhinitis or asthma, and had negative skin prick test to a panel of allergens.